Natural Frequency of Buildings and Resonance Phenomenon: Impacts on Structural Design - yahya kurniawan kurni; Hivaldo Ricky Sitorus; Muhammad Edy Suwarno; Jumiati Ratutoli Ratu (METALOGRAM, 2025)
This piece explores the inherent frequency of buildings and the associated resonance effect, emphasizing their crucial roles in structural engineering. Grasping the natural frequency is vital for forecasting how structures react to dynamic forces such as earthquakes and strong winds. The research underscores the need to take into account the height and weight of buildings, as these elements affect their natural frequency and subsequently influence their performance during seismic activities. Through both theoretical insights and real-world instances including the Mexico City earthquake of 1985 and a building collapse the article illustrates the dangers posed by resonance when a structure's natural frequency coincides with external vibration frequencies. A particular case study is highlighted to demonstrate superior structural and aerodynamic design approaches aimed at reducing resonance due to seismic and wind effects. This study aspires to act as a guide for engineers and architects in recognizing and tackling resonance-related issues to improve the safety and durability of tall buildings.